Look east to act east policy implications for India's Northeast - Das, Gurudas; Thomas, C. Joshua (Routledge, 2016)
This volume captures the success of India's Look East Policy (LEP) in promoting economic engagement wit neighbouring countries in Asia and simultaneously its limitations in propelling growth in the bordering North Eastern Region - India's bridge head to South East Asia. It analyses the instrumental role of LEP in bringing a tectonic shift in India's foreign trade by redirecting the focus from the West to the East, thus leading to a fundamental change in the nature of India's economic interdependence. Besides discussing foreign trade, it expounds as to how LEP made India play an important role in the emerging Asian security architecture and liberated Indian foreign policy from being centred on South Asia. The essays also enumerate the reasons for LEP's failure in the North Eastern Region and chart out actionable programmes for course correction that might be factored into its latest edition - the Act East Policy. This book will interest scholars and researchers of international relations, international trade and economics, politics, and particularly those concerned with Northeast India.